2011
DOI: 10.4321/s1886-36552011000400005
|View full text |Cite
|
Sign up to set email alerts
|

What do children with cancer know about their medications?

Abstract: ObjectiveTo explore the health literacy of children diagnosed with Acute Lymphoblastic Leukemia (ALL) through their knowledge of their medications.MethodsWithin the Basic Interpretive approach to qualitative research, semi-structured interviews were conducted with children from ages 6 to18 years (n=16) between May and September 2009 to determine their knowledge of medication properties, medication habits and medication teaching. REB approval was obtained.ResultsThe younger children (mean age 7.5 years) correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In which 16 patients, ages 6 through 18 years were interviewed, 73% of the children reported that the physician directed medication education solely to the parents, and 64% said that they were only sometimes or never present in the room while this occurred. 9 These results are supported by a review conducted by Coyne (2008), where they found that many kids also felt neglected, mitigated, or as though their wishes were not elicited. 5 Children are often overlooked for several reasons, mainly because they are usually not engaged in discussion, they are distracted by their tablets/phones (as noted by some health care providers during this study), or because it is difficult for the healthcare provider to accurately assess the child's competency and ability to comprehend the information.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In which 16 patients, ages 6 through 18 years were interviewed, 73% of the children reported that the physician directed medication education solely to the parents, and 64% said that they were only sometimes or never present in the room while this occurred. 9 These results are supported by a review conducted by Coyne (2008), where they found that many kids also felt neglected, mitigated, or as though their wishes were not elicited. 5 Children are often overlooked for several reasons, mainly because they are usually not engaged in discussion, they are distracted by their tablets/phones (as noted by some health care providers during this study), or because it is difficult for the healthcare provider to accurately assess the child's competency and ability to comprehend the information.…”
Section: Introductionmentioning
confidence: 69%
“…How the drugs work may be a bit more challenging, but the results of our previous study did determine that children of various ages want to know more about how their medicines work, especially the teenage population. 9 The pharmacist should review how the drug works with the child in a manner appropriate for the child's comprehension level. Teenagers are capable of abstract thought and would understand how the drug works inside the body, but some younger children may also be able to comprehend this.…”
Section: Discussionmentioning
confidence: 99%